2011
DOI: 10.4314/sajas.v41i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of whole cottonseed on performance, carcass characteristics and intestinal morphology of Zandi lambs

Abstract: ______________________________________ __________________________________________ tcartsbAThe present study was conducted to determine the effect of including different levels of whole cottonseed (WCS) in the finishing diet of lambs on their dry matter intake (DMI), live weight gain, feed conversion ratio (FCR, kg feed/kg gain), carcass characteristics and small intestinal morphology. Twenty Zandi male lambs (29.8 ± 1.6 kg body weight) were assigned to one of four diets in a completely randomized experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
3
0
1
Order By: Relevance
“…The inclusion of baker's yeast improved the value of gain of producing a buck in this study as reflected in the live weight gains. This is contrary to previous studies of Absalan et al (2011) and Yakubu et al (2017), who advised minimal inclusion of cotton products in goat diet. The result of this study clearly shows that the addition of baker's yeast in cotton products based diets improved weight gain that translate to more economic gain to the farmer.…”
Section: Cost Per Kilogram Live Weight Gain Of Feeding Crushed Whole ...contrasting
confidence: 96%
“…The inclusion of baker's yeast improved the value of gain of producing a buck in this study as reflected in the live weight gains. This is contrary to previous studies of Absalan et al (2011) and Yakubu et al (2017), who advised minimal inclusion of cotton products in goat diet. The result of this study clearly shows that the addition of baker's yeast in cotton products based diets improved weight gain that translate to more economic gain to the farmer.…”
Section: Cost Per Kilogram Live Weight Gain Of Feeding Crushed Whole ...contrasting
confidence: 96%
“…It is relevant to compare this figure with that found by Sahin et al (2003) who found that TMR and FCF in Awassi lambs were not affect on hot carcass weight and dressing percentage. The fact that there were no differences between treatments in terms of internal organ weights indicate that lambs used in the present study had a similar metabolic rate, as reported by Absalan et al (2011).…”
Section: Resultssupporting
confidence: 81%
“…The weights of the liver, spleen, head, and stomach with empty intestines (kg) in the T 4 and T 3 groups were significantly (p < 0.05) higher than in the other groups, and the findings were close to the range considered to be conventional for Mecheri lambs and consistent with a previous study [46], and they observed higher weights of liver, stomach with empty intestines, and heads in Mecheri lambs fed with 1.5 percent concentrate supplementation on body weight. Furthermore, these results were equivalent to those reported in Zandi lambs offered a higher amount of cotton seed [43]. In terms of the percentage of wholesale cuts between the fore and hind quarters, there was no noticeable difference between treatment groups, and similar findings were observed in Mecheri [45] and Nellore crossbred lambs [47].…”
Section: Carcass Characteristicssupporting
confidence: 84%
“…According to the results of the current investigation, lambs given 50 and 75 percent CGT of the roughage potion displayed improved carcass weight and dressing percentage compared to the control group. The dressing percentage in the current study was similar to that noticed in lambs of several sheep breeds, viz., Assaf lambs (50.6%) [42], Zandi lambs (50.6%) [43], and cross-bred lambs (50%) [44]. Similar to this, steers [12] consuming the CGT-based diet had heavier hot carcass weights (396 kg) and higher dressing percentages (62.7%) than steers ingesting the control diet without CGT (382 kg and 62.2%).…”
Section: Carcass Characteristicssupporting
confidence: 57%